Review Of Psychological And Economic Aspects Of Experience In Conduct Ners Further Study - Eni Kusyati; Rini Wijayanti; Julvainda Eka Priya Utama (Sekolah Tinggi Ilmu Kesehatan (STIKes) Karya Husada Semarang, 2023)
Santa Elisabeth Hospital has 422 nurses and 152 nurses graduates. Of the total nurses, 68 people are Diploma III in Nursing who have completed Nursing education. Legally, formal nursing professional education is regulated in Nursing Act number 38. Nurses have a strong scientific foundation, good psychomotor skills and professionalism in providing nursing care. The aim is to explore the experience of advanced studies in terms of psychological and economic aspects. Qualitative research method with phenomenological design. Data was collected through focus group discussions with structured interview guides. The participants were nurses in the further study process, a total of six nurses using a purposive sampling technique. The results show that there are two themes in the psychological aspect and two themes in the economic aspect. Conclusion: Experience from the psychological aspect: 1) Statement of motivation for further studies: enthusiasm for further studies comes from oneself and family, motivation to improve one's abilities, motivation comes from friends who are elderly but still enthusiastic for further studies. 2) further studies stressor: the workload increases, namely lectures and studies, stress arises in allocating time. Based on the experience of the economic aspect, the theme was found 1) sources of costs: borrowing from banks, financed by the hospital, money from savings 2) Opinion of costs: cost of further study for nurses is expensive, fees for nurses are standard.Keywords: economy; psychological; advanced studies nurseTinajuan Pengalaman Aspek Psikologi Dan Ekonomi Dalam Menjalani Studi Lanjut Ners ABSTRAK RS Santa Elisabeth memiliki 422 orang perawat dan 152 orang lulusan Ners. Dari total ners, 68 orang adalah Diploma III Keperawatan yang telah menyelesaikan pendidikan Ners. Secara legal formal pendidikan profesi keperawatan diatur dalam Undang-Undang Keperawatan nomor 38. Ners mempunyai landasan keilmuan yang kuat, kemampuan psikomotor yang baik dan sikap profesionalisme di dalam memberikan asuhan keperawatan. Tujuan mengeksplorasi pengalaman study lanjut ners ditinjau dari aspek psikologi dan ekonomi. Metode penelitian kualitatif dengan desain fenomenologi. Data dikumpulkan melalui focus group discussion dengan panduan wawancara terstruktur. Partisipan adalah perawat proses study lanjut ners sejumlah enam dengan teknik sampel purposive sampling. Hasil menunjukkan aspek psikologis ditemukan dua tema dan aspek ekonomi ditemukan 2 tema. Kesimpulan : Pengalaman dari aspek psikologis : 1) Pernyataan movitasi studi lanjut : semangat studi lanjut berasal dari diri sendiri dan keluarga, motivasi meningkatkan kemampuann, motivasi berasal dari temen yang sudah usia lanjut tapi masih semangat untuk studi lanjut. 2) stressor studi lanjut : beban kerja menjadi bertambah yaitu kuliah dan belajar, muncul stress dalam membagi waktu. Pengalaman aspek ekonomi ditemukan tema 1) sumber biaya : meminjam dari bank, dibiayai pihak rumah sakit, uang dari tabungan 2) Pendapat biaya : biaya studi lanjut ners mahal, biaya ners standar. Kata Kunci : ekonomi; psikologis; studi lanjut ners